Making easy listening : material culture and postwar American recording - Anderson, Tim J. (Commerce and mass culture series., 2006)
In Making Easy Listening, Tim J. Anderson analyzes the period between the Second World War and the mid-1960s that saw the American music industry engaged in a fundamental transformation in how music was produced and experienced. Anderson presents a social and cultural history of musical production that aims to understand how recording technologies influence musicians', as well as listeners', lives.